2018
DOI: 10.1177/2047487318759119
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sporadic non-syndromic thoracic aortic aneurysms: 1. Deregulation of Jagged/Notch 1 homeostasis and selection of synthetic/secretor phenotype smooth muscle cells

Abstract: Background Sporadic non-syndromic thoracic aortic aneurysms (SNSTAAs) are less well understood than familial non-syndromic or syndromic ones. The study aimed at defining the peculiar morphologic and molecular changes occurring in the media layer of SNSTAAs. Design This study was based on a single centre design. Methods Media layer samples taken from seven carefully selected SNSTAAs and seven reference patients (controls) were investigated via quantitative polymerase chain reaction, proteomics-bioinformatics, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…However, Notch signaling antagonizes TGF-β signaling by reducing the expression of TGF-β receptor II via the induction of miR145 [180]; in turn, TGF-β antagonizes Notch signaling by decreasing the expression of Notch3 [181]. The expression of Notch ligands and receptors is dysregulated in TAA, and defective Notch signaling has been associated with TAA that develops in patients with malformations of the aortic valve [175,182,183].…”
Section: Notch Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Notch signaling antagonizes TGF-β signaling by reducing the expression of TGF-β receptor II via the induction of miR145 [180]; in turn, TGF-β antagonizes Notch signaling by decreasing the expression of Notch3 [181]. The expression of Notch ligands and receptors is dysregulated in TAA, and defective Notch signaling has been associated with TAA that develops in patients with malformations of the aortic valve [175,182,183].…”
Section: Notch Signalingmentioning
confidence: 99%
“…In mouse models, Notch1 haploinsufficiency causes aortic dilation in mice of a permissive genetic background (129S6) and exacerbates aortic root pathology of MFS mouse models, independently of aortic valve defects [329]. Although the mechanisms by which loss of Notch signaling causes TAA remain unclear, defective developmental interactions between endothelial cells and VSMCs, and direct effects on VSMC phenotype have both been proposed [175,183,330]. Notably, whereas Notch signaling appears to be protective in TAA, it tends to exacerbate inflammation-driven AAA [175,331,332].…”
Section: Notch1mentioning
confidence: 99%
“…We reported that in SNSTAAs an increased JAG1NOTCH1 signalling was interfered by the proteolysis of JAG1 and the formation of a dominant-negative soluble JAG1 fragment. 28 The reduced availability of MAGP1 protein we observed would further lessen JAG1NOTCH1 signalling and its positive consequences on tissue remodelling in the media layer of SNSTAAs. Previous studies showed that the MAGP1-deficient mouse suffers from two healing defects: a delayed clot formation in response to endothelial damage, and a delayed healing of incisional skin wounds.…”
Section: Changes In Ecm Components: Magp1 and Testican2mentioning
confidence: 80%
“…The VSMC-specific elimination of Jagged1 [ 116 ] or the combined loss of Notch3 and specific ablation of Notch2 in VSMCs [ 117 ] results in a PDA-like phenotype in mice. Furthermore, NOTCH1 gene variants were observed in patients with aortic coarctation and aortic aneurysm (for a review see [ 118 ]), and aberrant expression of Notch pathway genes was noted in patients with thoracic aortic aneurysm [ 119 , 120 ].…”
Section: Notch and Vascular Diseasementioning
confidence: 99%